2014
DOI: 10.1159/000362898
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Findings of Tunisian Patients with RASopathies

Abstract: Noonan syndrome (NS) and related disorders, which are now summarized under the term RASopathies, are caused by germline mutations in genes encoding protein components of the Ras/mitogen-activated protein kinase pathway. In this study, we evaluated the clinical and molecular spectrum of 21 Tunisian patients, recruited by a cardiology unit, for whom RASopathy diagnosis was suspected by clinical geneticists. Overall, 19 patients had a clinical diagnosis of NS and 2 were classified as having Cardiofaciocutaneous (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…We did not detect any pathogenic variants in the C terminal region, which is consistent with most other studies [17].…”
Section: Genotype-phenotype Correlationsupporting
confidence: 93%
See 3 more Smart Citations
“…We did not detect any pathogenic variants in the C terminal region, which is consistent with most other studies [17].…”
Section: Genotype-phenotype Correlationsupporting
confidence: 93%
“…Our cohort had CHD (in 84% of patients with pathogenic variants) mainly consisting of right-sided cardiac anomalies [57]. Studies by Zenker [11], Tartaglia [66], Louati [17] and Ferrero [28] also reported high frequency of CHD. The most frequently occurring pathogenic variants in our cohort, c.922A > G and c.923A > G, both of which change the same amino acid (Asn308), were seen in 22 patients, including a three-generationaffected pedigree.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 61%
See 2 more Smart Citations